INQUENCING-BASED LEARNING POTENTIAL TO PRACTICE METACOGNITIVE SKILLS - Andik Andriyanto; Jan Hendriek Nunaki; Insar Damopolii (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Tujuan penelitian ini adalah mengkaji potensi PBI untuk melatih keterampilan metakognitif siswa SMA. Sebanyak 63 siswa SMA menjadi sample dalam penelitian eksperimen ini. 30 siswa berada pada kelas eksperimen. 33 siswa berada di kelas control. Siswa diukur metakognitifnya menggunakan tes uraian berjumlah sembilan item. Data perbedaan metakognitif siswa dihitung menggunakan Mann-Whitney tes. Hasil analisis diperoleh bahwa metakognitif siswa di awal ada sama (sig. > 0.05). Hasil analisis metakognitif akhir mengungkap bahwa metakognitif siswa kelas eksperimen dan control adalah berbeda (sig.<0.05). Penelitian ini menyimpulkan bahwa perbedaan keterampilan metakognitif siswa disebabkan oleh perbedaan pembelajaran yang digunakan. Siswa terlatih lebih baik metakognitifnya dengan pembelajaran inkuiri dibanding siswa di bukan pembelajaran inkuiri. Riset ini merekomendasikan bahwa guru dapat menggunakan pembelajaran inkuiri untuk memperbaiki keterampilan metakognitif siswanya.Abstract: The aimed of this article was to explore the potential of IBL to train high school students' metacognitive skills. A total of 63 high school students were sampled in this experimental study. Thirty students were in the experimental group, and thirty-three students were in the control group. Students were measured metacognitive using an essay test totaling nine items. Data on students' metacognitive differences were calculated using the Mann-Whitney assess. The finding of the analysis showed that the students' metacognitive values at the beginning were equal (sig.>0.05). The final metacognitive analysis results revealed that the students metacognitive of the experimental and control classes were different (sig.<0.05). This study concluded that differences in students' metacognitive skills were caused by differences in the learning used. Students with trained inquiry learning have better metacognitive skills than students in non-inquiry learning. This research recommends that teachers use inquiry learning to improve their students' metacognitive skills.